Subclavian artery stenosis in hemodialysis patients: a case series and review of the literature - Pu, Wenshen; Yang, Jingjie; Lai, Qiquan; Zhou, Yu; Tu, Bo; Wang, Bingjie; Wan, Ziming (Frontiers in Pharmacology, 2026)
Subclavian artery (SA) stenosis is an uncommon but important cause of arteriovenous fistula (AVF) dysfunction in hemodialysis patients, yet its diagnosis is frequently delayed because symptoms are nonspecific and often attributed to venous lesions. We report a case series of nine hemodialysis patients diagnosed with SA stenosis or occlusion at a tertiary nephrology center between 2019 and 2023, detailing their clinical presentations, imaging findings, treatments, and outcomes, and summarize relevant literature to contextualize our findings. All patients had left-sided AVFs, mostly radial-cephalic, with a median interval of 3.4 years from dialysis initiation to diagnosis. Presentations included reduced AVF blood flow, occlusion, diminished thrill, and significant interarm systolic blood pressure discrepancy, two patients reported neurological symptoms. Duplex ultrasound often revealed reduced brachial artery flow and/or reversed vertebral artery flow, while lesions were most frequently located at the SA origin. Atherosclerosis was the predominant etiology, followed by Takayasu arteritis. Seven patients underwent percutaneous transluminal angioplasty (PTA), six with stenting, achieving restoration of AVF flow and symptom resolution, two patients declined intervention but maintained adequate dialysis. Literature review confirmed that high-flow AVFs and atherosclerosis increase the risk of SA stenosis and that endovascular revascularization is the preferred treatment when access dysfunction is present. Our findings highlight the importance of early screening with bilateral blood pressure measurement and duplex ultrasound in patients with unexplained access dysfunction, and we outline a practical diagnostic and treatment approach that may help improve dialysis adequacy and reduce morbidity in this high-risk population.